2018
DOI: 10.1002/chem.201803749
|View full text |Cite
|
Sign up to set email alerts
|

Earth‐Abundant Transition‐Metal‐Based Electrocatalysts for Water Electrolysis to Produce Renewable Hydrogen

Abstract: Fundamentals of water electrolysis, and recent research progress and trends in the development of earth-abundant first-row transition-metal (Mn, Fe, Co, Ni, Cu)-based oxygen evolution reaction (OER) and hydrogen evolution (HER) electrocatalysts working in acidic, alkaline, or neutral conditions are reviewed. The HER catalysts include mainly metal chalcogenides, metal phosphides, metal nitrides, and metal carbides. As for the OER catalysts, the basic principles of the OER catalysts in alkaline, acidic, and neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
150
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(150 citation statements)
references
References 160 publications
(468 reference statements)
0
150
0
Order By: Relevance
“…Pan et al constructed TiO 2 p-n homojunction to realize enhanced PEC H 2 evolution performance. Virtually, it is revealed that most of the excellent PEC water splitting cocatalysts are electrocatalysts, [18][19][20] such as transition metal dichalcogenides (TMDs), [21][22][23][24][25] phosphorous metal compounds, [26][27][28] metal oxides, [29][30][31][32] metal hydroxides, [29,33] etc. [16] Alternatively, engineering cocatalysts on the surface of photoelectrodes gradually came to sight recently, as the existence of cocatalysts can bring about the reduced overpotential, accelerated reaction kinetics, enriched active sites, and suppressed corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al constructed TiO 2 p-n homojunction to realize enhanced PEC H 2 evolution performance. Virtually, it is revealed that most of the excellent PEC water splitting cocatalysts are electrocatalysts, [18][19][20] such as transition metal dichalcogenides (TMDs), [21][22][23][24][25] phosphorous metal compounds, [26][27][28] metal oxides, [29][30][31][32] metal hydroxides, [29,33] etc. [16] Alternatively, engineering cocatalysts on the surface of photoelectrodes gradually came to sight recently, as the existence of cocatalysts can bring about the reduced overpotential, accelerated reaction kinetics, enriched active sites, and suppressed corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Additionally, utilization of different catalysts for HER and OER would further increase the cost due to the complicated process and extra equipment for manufacturing electrodes. [8] Additionally, utilization of different catalysts for HER and OER would further increase the cost due to the complicated process and extra equipment for manufacturing electrodes.…”
mentioning
confidence: 99%
“…The potential required to run the HER ( E HER ) can be defined in terms of the standard reduction potential ( E 0 = 0 V vs RHE) and the overpotential (η) via Equation EHER = E0 + η…”
Section: Resultsmentioning
confidence: 99%